Antibody responses to fusobacterium nucleatum proteins in prediagnostic blood samples are not associated with risk of developing colorectal cancer - Butt, Julia; Pawlita, Michael; Kaaks, Rudolf; Kühn, Tilman; Waterboer, Tim (Cancer epidemiology, biomarkers & prevention, 2019)
Background: There is a lack of prospective data on the potential association of Fusobacterium nucleatum (F. nucleatum) and colorectal cancer risk. In this study, we assessed whether antibody responses to F. nucleatum are associated with colorectal cancer risk in prediagnostic serum samples in the European Prospective Investigation into Nutrition and Cancer (EPIC) cohort. - Methods: We applied a multiplex serology assay to simultaneously measure antibody responses to 11 F. nucleatum antigens in prediagnostic serum samples from 485 colorectal cancer cases and 485 matched controls. Conditional logistic regression models were used to estimate odds ratios (ORs) and 95% confidence intervals (CI). - Results: We observed neither a statistically significant colorectal cancer risk association for antibodies to individual F. nucleatum proteins nor for combined positivity to any of the 11 proteins (OR, 0.81; 95% CI, 0.62-1.06). - Conclusions: Antibody responses to F. nucleatum proteins in prediagnostic serum samples from a subset of colorectal cancer cases and matched controls within the EPIC study were not associated with colorectal cancer risk. - Impact: Our findings in prospectively ascertained serum samples contradict the existing literature on the association of F. nucleatum with colorectal cancer risk. Future prospective studies, specifically detecting F. nucleatum in stool or tissue biopsies, are needed to complement our findings.
Gesehen am 24.01.2020